Czech Interwar Photography between Art, Society and Politics - Vogelová, Pavlína (METSZETEK Társadalomtudományi Folyóirat, 2018)
Interwar Czech photography in the cultural spectre from the viewpoint of media and technologyis related with penetration to various areas without intentionally directed nature of genres orstyles. Viewed in a context with the phenomena of new mass media, industrialization, leisuretime and general cultural and sociological relations in the spatio-temporal compression ofmodernity, photography plays a major role in forming modern culture in the 1920’s and 1930’s,in the “golden era of photography”. I have focused on the tendencies of photographic expression,influence and thinking after World War I. I considered it is important to point to reversed flowof ideas, i.e. from other fields of human activity towards photography, when this concerns toolswhere the development of new photographic was projected back to artistic and general sociallevels.